A study on dietary habits, health related lifestyle, blood cadmium and lead levels of college students - Shin, N.R., Myongji University, Yongin, Republic of Korea; Hyun, W.J., Joongbu University, Kumsan, Republic of Korea; Lee, H.M., Daejin University, Pocheon, Republic of Korea; Ro, M.S., Seoul Breast and Thyroid Clinic, Seoul, Republic of Korea; Song, K.H., Myongji University, Yongin, Republic of Korea (Nutrition research and practice, 2012)
This study was performed in order to investigate dietary habits, health related lifestyle and blood cadmium and lead levels in female college students. 80 college students (43 males and 37 females) participated in the survey questionnaires. Body weight and height, blood pressure, and body composition were measured. The systolic blood pressure of male and female students were 128.9 ± 13.9 and 109.8 ± 12.0, respectively. The diastolic blood pressure of male and female students were 77.1 ± 10.3 and 66.0 ± 6.9, respectively, showing that male students had significantly higher blood pressure than female students (P less than 0.001). The BMI of male and female students were 23.4 ± 3.3 and 20.2 ± 2.3, respectively. Most male students were in the range of being overweight. The dietary habits score of female students was significantly higher than that of male students (P less than 0.01). The blood cadmium level of male and female students were 0.54 ± 0.23 and 0.52 ± 0.36, respectively. There was no significant difference between male and female students. The blood lead level of male and female students were 1.09 ± 0.49 and 0.59 ± 0.45, respectively. The blood lead level of male students was significantly higher than that of female students (P less than 0.001). The blood cadmium level of smokers and nonsmokers were 0.69 ± 0.29 and 0.49 ± 0.29 respectively (P less than 0.05). The blood cadmium level of smokers was significantly higher than that of nonsmokers (P less than 0.05). The blood lead level of smokers and nonsmokers were 1.09 ± 0.43 and 0.80 ± 0.54, respectively. The blood lead level of smokers was significantly higher than that of nonsmokers (P less than 0.05). Therefore, proper nutritional education programs are required for college students in order to improve their dietary and health related living habits.